Vicarious Learning under Implicit Contracts - Choi, Jongwoon (Willie); Hecht, Gary; Tafkov, Ivo D.; Towry, Kristy L. (The Accounting Review, 2016)
ABSTRACT Employee contracts often allow for managerial discretion, such that the manager decides after observing an employee's performance how that employee will be rewarded or penalized. Importantly, the effects of such evaluation outcomes can extend beyond the employee(s) directly affected, because such outcomes can be observed by other employees within the firm. The net effect of such vicarious learning as an indirect control depends on the inferences employees make after observing a peer's evaluation outcome. In this study, we use an experiment to investigate whether the inferences observer-employees make about how managers evaluate and reward employee behavior depend on whether the valence of the observed outcome is positive or negative. Using the setting of a strategic performance measurement system, we test and find support for a causal model, in which the valence of the observed outcome influences observer-employees' inferences and subsequent behavioral focus via their psychological distance from, and their construal of, the observed outcome. Our results suggest that how observer-employees respond after observing a peer employee's evaluation outcome is asymmetric. Specifically, when contemplating their own behavior, employees who observe positive outcomes focus on the performance measures within the strategic performance measurement system, whereas those who observe negative outcomes focus on the underlying strategic construct.